Análise do impacto do carregamento de veículos elétricos na rede elétrica - Wilke, Davi Pavezi (2023)
The increasing adoption of electric vehicles (EVs) as a sustainable transportation alternative has driven the need for recharging infrastructure capable of meeting the expanding demand. However, the significant rise in the number of EVs brings challenges to electric energy management and network stability. In this context, this work aims to analyze the impact of EV charging on the grid. Through the analysis of EV load profiles, fluctuations in demand and load concentration will be investigated. We will identify penetration percentages in the network that can lead to overloads in distribution lines and excessive voltage drops. To achieve these goals, a methodology was used of selecting consumer units with EVs for the simulation analysis of EV charging in the OpenDSS software, supported by Python programming. The results obtained will allow us to identify critical demand charging patterns and propose appropriate energy management strategies. It is expected that this study will contribute to advancing knowledge in the field of energy management at EV charging stations, providing relevant information for energy utilities, industry companies, and researchers interested in the efficient and sustainable integration of EVs into the electrical grid.